Microalgae to energy: biomass recovery and pre-treatments optimisation for biogas production integrated with wastewater nutrients removal - Ometto, Francesco (Cranfield University, 2014)
The increasing concern about water quality and energy demand promotes the development of innovative and low-cost processes to improve the nutrient uptake and energy efficiency of existing wastewater treatments (WWT). In this context, the inclusion of a microalgae system (MAS) in the flowsheet of a WWT plant represents a sustainable alternative to conventional technologies, as it combines a low-cost nutrient uptake system with the production of biomass suitable for biofuel production. However, at present, the energy required to cultivate and process the algae cells is often too high to justify their use. The adoption of a low energy harvesting system and an efficient energy conversion process are the sine qua non requirements to guarantee the sustainability of the process. In this thesis, current and innovative harvesting technologies for large scale applications have been reviewed to identify the optimal working conditions of each system and their link to the main characteristics of the algae suspension. In particular, the performance of the Ballasted Dissolved Air Flotation (BDAF) system was investigated using different algae and compared to the conventional Dissolved Air Flotation (DAF). BDAF was demonstrably a very viable harvesting method where the use of floating microspheres as ballasting agents allowed significant coagulant savings, reduced the level of energy dissipation within the flotation chamber, and lowered the overall carbon emissions and the process costs. Cont/d.
Keywords: harvesting; Algogenic Organic Matter (AOM); pre-treatments; microalgae cell wall degradation; energy balance; carbon footprint